Stipulation of the Possibility to Use Embryonic Neuronal Cells when Treating Organospecific Autoimmune Diseases - Goltsev, A. N.; Babenko, N. N. (Problems of Cryobiology and Cryomedicine, 2006)
There was studied the possibility of this pathology treatment with intraperitoneal introduction of native and cryopreserved embryonic neuronal cells (ENCs) in the model of allergic encephalomyelitis as experimental analogue of multiple sclerosis (MS). The efficiency of performed therapy is established to be determined both by morphofunctional status of transplants and their introduction terms, i.e. to the 7thÂ and 14thÂ day of the pathological process development. It has been noted that cryopreserved ENCs (cENCs) in contrast to native ENCs (nENCs) during the introduction had correction peculiarities of clinical and neurological status of animals, immune regulatory index, killer activity of splenocytes and content of finely dispersed circulating immune complexes (fCIC) in blood serum.